2010
DOI: 10.1600/036364410x493340
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Diploid Members of the Medicago sativa (Fabaceae) Species Complex Based on Chloroplast and Mitochondrial DNA Sequences

Abstract: The Medicago sativa species complex includes tetraploid cultivated alfalfa and several other diploid and tetraploid taxa that are recognized either as subspecies of M. sativa or as separate species. The two principal diploid taxa are "caerulea," with purple flowers and coiled pods, and "falcata" with yellow flowers and falcate pods. To understand the evolutionary relationships among taxa in the complex, sequence variation in two noncoding regions of cpDNA ( rpl20 -rps12 and trnS -trnG spacers) and three region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 59 publications
5
35
0
Order By: Relevance
“…Medicago sativa is relatively unusual among flowering plants in having predominantly paternal transmission of cpDNA (Schumann and Hancock, 1989; Smith, 1989; Masoud et al, 1990). Here we follow up our finding of chloroplast haplotype differentiation among the blue‐ and yellow‐flowered diploid members of this species (Havananda et al, 2010). We explore genetic diversity among tetraploid members of M. sativa using the same cpDNA regions to elucidate origins of tetraploids and to understand patterns of gene flow within and between ploidal levels.…”
Section: Principal Characters Used In Distinguihing Members Of Medicasupporting
confidence: 64%
See 3 more Smart Citations
“…Medicago sativa is relatively unusual among flowering plants in having predominantly paternal transmission of cpDNA (Schumann and Hancock, 1989; Smith, 1989; Masoud et al, 1990). Here we follow up our finding of chloroplast haplotype differentiation among the blue‐ and yellow‐flowered diploid members of this species (Havananda et al, 2010). We explore genetic diversity among tetraploid members of M. sativa using the same cpDNA regions to elucidate origins of tetraploids and to understand patterns of gene flow within and between ploidal levels.…”
Section: Principal Characters Used In Distinguihing Members Of Medicasupporting
confidence: 64%
“…However, much less is known about other tetraploids in this species or about the diploids hypothesized to have given rise to them and to alfalfa, despite the use of some of these taxa in alfalfa breeding programs. Indeed, it is still an open question whether there may be taxonomic allopolyploids in this species, given the morphological diversity and controversial taxonomic history of diploid members (e.g., Havananda et al, 2010).…”
Section: Principal Characters Used In Distinguihing Members Of Medicamentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive examination of wild diploid germplasm using simple sequence repeat (SSR) markers showed that falcata and caerulea accessions are clearly distinct, with hybrids falling in between the separate parental groups [10,11]. Falcata and sativa are similarly distinct, based on numerous experiments conducted on tetraploid populations [9,12,13].…”
Section: Alfalfa Origins and Genetic Diversitymentioning
confidence: 99%